Creativity for multiculturalism: the artistic and educational action for developing borderland identity - Bieńkowska, Małgorzata (Creativity Studies, 2021)
The purpose of this text is to showcase creativity in action, creativity that has been directed to fostering mutual understanding and cooperation in a culturally diverse environment – in a region that has seen ethnic conflict. The text is devoted to the analysis of the work of two interrelated organisations – the Borderland Foundation, Poland and the Center for Borderland Arts, Cultures and Nations, Poland – which for decades have been working innovatively on a complex history, together with the local community. This is a history that includes nationally and religiously diverse groups. Experiences with the local community have provided the inspiration for the Borderland Foundation and the Centre for Borderland Arts, Cultures and Nations for further creative work in art, education and history focussed on the phenomenon of borderland identity. The text is based on an analysis of both institutions’ websites, as well as interviews with their team members and project participants.